Associations between evidence-based practice and mental health outcomes in child and adolescent mental health services. (April 2016) - Deighton, Jessica; Argent, Rachel; De Francesco, Davide; Edbrooke-Childs, Julian; Jacob, Jenna; Fleming, Isobel; Ford, Tamsin; Wolpert, Miranda
The effectiveness of evidence-based practice in the treatment of children with conduct disorder ( n = 186) or emotional disorders ( n = 490) in routine care was examined using naturalistic, previously collected data from 30 child and adolescent mental health services. Repeated measures analysis of covariance was used to compare the outcomes of children who received parent training for conduct disorder and cognitive behavioural therapy for emotional disorders (evidence-based practice) with children who did not receive these treatments (non-evidence-based practice). There was a relatively low occurrence of evidence-based practice, particularly for children with conduct disorder. Both the evidence-based practice and non-evidence-based practice groups improve over time, with moderate effect sizes, and there were greater improvements associated with evidence-based practice for children with emotional disorders, based on child self-reported symptoms but not on parent report. In the present sample, significant differences were not found for conduct disorder. Findings provide tentative support for evidence-based practice for the treatment of emotional disorders in routine care settings.